The design of national fiscal frameworks and their budgetary impact - Carolin Nerlich; Wolf Heinrich Reuter (European Central Bank (ECB), 2013)
This study analyses the link between fiscal frameworks and their budgetary impact. We look at different features of national numerical fiscal rules in combination with fiscal councils and medium-term budgeting frameworks. We construct our own time-varying dataset for national fiscal frameworks for the period 1990-2012 covering all 27 EU Member States and estimate a dynamic panel on aggregate and disaggregated fiscal policy variables. We find strong support that numerical fiscal rules help to improve the primary balance, and that the budgetary impact can be further strengthened when supported by independent fiscal councils and an effective medium-term budgeting framework.
Keywords: E61; E62; H60; 330; fiscal council; fiscal framework; Fiscal Policy; fiscal rules; medium term budgeting framework